A computational method for detection of ligand-binding proteins from dose range thermal proteome profiles - Nils Kurzawa (Nature Portfolio, 2020)
2D-thermal proteome profiling (2D-TPP) is a powerful assay for probing interactions of proteins with small molecules in their native context. Here the authors provide a statistical method for false discovery rate controlled analysis for 2D-TPP applications.